Exploratory transcriptomic analysis of low-grade oral epithelial dysplasia and oral squamous cell carcinoma in Chilean patients - Mateus José Dutra; Patricio Miranda Cortes; Valentina Fernanda Fernández Díaz; Mauricio Alejandro Sáez Venegas; Sebastián Morales-Pison; Wilfredo Alejandro González-Arriagada; Ricardo Fernández-Ramires; Daniela Adorno-Farias (Molecular Biology Reports, 2026)

Returning to the playground: Making molecular tests easier - Isaac Rodríguez-Guerrero; Sofía María Blanco-Guzmán; Samuel Rodríguez-Guerrero; Antonio Rascón-Careaga; Alejandro Monserrat García-Alegría; Viridiana Rossell Gallegos-Miranda; José María Gastélum-Cano (Next Research, 2026)

Design and evaluation of two heuristic-based interactive controllers for selective apple harvest - Miranda Cravetz; Alejandro Velasquez; Jared Northrop; Cindy Grimm; Joseph R. Davidson (Computers and Electronics in Agriculture, 2026)

Influence of nurse plant canopy and cactus size on the production and distribution of reproductive structures of Pilosocereus leucocephalus - Antonio Miranda-Jácome; Vinicio J. Sosa; Alejandro Vázquez (Journal of Arid Environments, 2026)

Hematological responses of understory birds to haemosporidian parasites across land use and seasonal gradients in a cloud forest ecosystem of Veracruz, Mexico - Sandra Rocío Hernández-Soto; Daniel Gonzalez-Tokman; Alejandro Espinosa de los Monteros; Sergio Albino Miranda; Diego Santiago-Alarcon (Journal of Ornithology, 2026)

Infraspecific anatomical variation of Vanilla planifolia Andrews in the Totonacapan region, Mexico - Wooden Victor Velasco-Tapia; Estela Sandoval-Zapotitla; Ma.Concepción Guzmán-Ramos; Víctor Manuel Salazar-Rojas; Jorge Campos; Olga Andrea Hernández-Miranda; Manuel Alejandro Vallejo-Zamora; Miguel Ángel Acosta; Braulio Edgar Herrera-Cabrera (Flora, 2026)

Seminal Quality Variation in Chirostoma humboldtianum During an Annual Cycle and Cryopreservation Effect - Jesús Dámaso Bustamante-González; Gerardo Figueroa-Lucero; María Cecilia Hernández-Rubio; Judith Sarai Baca-Alejo; Edith Arenas-Ríos; Araceli Cortés-García; Leticia González-Núñez; Mariela Adriana Ydiaquez-Miranda; Alejandro Ávalos-Rodríguez (Fishes, 2026)
Chirostoma humboldtianum is an endemic atherinopsid from Mexico that has been of high socio-cultural and economic importance since pre-Hispanic times. It was the first ictic species from Mexico described for science, and it is considered the basal species that gave rise to a nominal group known as white fish or silversides. The aim of this research was to analyze semen quality in relation to breeding fish size and its effect on sperm cryopreservation during an annual cycle. Sexually mature males were collected from January to December 2023, in San Felix dam, Tiacaque, Mexico State, Mexico. The water temperature was measured, and the photoperiod was obtained from the Instituto Nacional de Geografía y Estadística (INEGI). Males were classified into two groups of total length (TL) after analyzing the variation in TL through a size histogram: (G1) 9–13 cm and (G2) longer than 13 cm. Semen volume (µL), sperm concentration (cells µL−1), and motility percentage (%) were determined in all individuals of each group. Likewise, eight straws were cryopreserved per month per group, each one with 10 µL of semen from a mixture of three randomly selected individuals and cryopreserved at −196 °C for 72 h. The post-thawing motility percentage was subsequently verified. Males produce semen continuously all year round, with two periods of higher volume, March and June–August, defining two reproductive periods. The beginning of the first one coincides with the increase in water temperature, from 13 ± 2 to 18 °C. Males with a length more than 13 cm had a higher semen production compared to smaller males (17.33 ± 7.34 and 12.52 ± 4.41 µL, respectively, p 0.05) (G1 = 1.35 ± 0.36 × 106 µL−1) (G2 = 1.31 ± 0.35 × 106 µL−1). In addition, fresh sperm motility was high in both groups (G1 = 96 ± 3%, G2 = 97 ± 4%) (p > 0.05). The highest sperm concentrations were observed in March to July, through to October for both groups (p > 0.05), while post-thaw sperm motility decreased by about 50% (G1 = 45 ± 4%) (G2 = 46 ± 6%) during the annual cycle (p > 0.05). The largest post-thaw motility was observed in March and from July to September in G1 and in March and from June to October in G2. Analysis of semen quality throughout the annual cycle reveals aspects of the reproductive biology of C. humboldtianum, including two reproductive peaks and continuous semen production.

DFT study of electronic properties of Ge nanowires with Na as potential anodic materials - Jose Antonio Moreno-Banda; Fernando Salazar; Alejandro Trejo-Baños; Álvaro Miranda; Luis Antonio Pérez; Miguel Cruz-Irisson (Chemical Engineering Journal, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

New evidence of oxidative foliar photo-necrosis caused by pigments from phyto-pathogenic fungi: hydroxyl-anthraquinones as fungal photo-toxins - Roberto Hernández-Chacón; Ricardo Tovar-Miranda; Arturo Coaviche-Yoval; Manuel E. Medina; Irene Lagunes; Alejandro Salinas-Castro; Ángel Trigos (Physiological and Molecular Plant Pathology, 2026)

Grain type influences the assembly of the intestinal bacterial community and generates a fitness cost in the maize weevil, Sitophilus zeamais, Motschulsky 1855 (Coleoptera: Curculionidae) - Essicka García-Saldaña; Edgar Guevara-Avendaño; Isabel Soto-Llanquitruf; Felipe Barrera-Méndez; Olinda Velázquez-López; Mizraim Olivares-Miranda; Ioreni Margarita Hernández-Velázquez; Jesús Alejandro Zamora-Briseño (Journal of Stored Products Research, 2026)

Emergent Salmonella enterica serovar Infantis forms a monophyletic lineage shaped by geographic structuring - Alejandro Piña-Iturbe; Daniel Tichy-Navarro; Josefina Miranda-Riveros; María José Navarrete; Andrea I. Moreno-Switt (International Journal of Food Microbiology, 2026)

The Current State of Research on Pejerrey ( Odontesthes bonariensis ) Physiology and Challenges for Aquaculture Development - Alejandro S. Mechaly; Leandro A. Miranda; Juan I. Fernandino; Luis F. Canosa; Juan I. Bertucci; Paula Vissio; Daniela I. Pérez Sirkin; María P. di Yorio; María R. Perez; Gabriela C. López; Pedro Gómez‐Requeni; E. Mayra Toledo‐Cuevas; et al. (Reviews in Aquaculture, 2026)
Pejerrey is a native fish of the Pampas with relevance in aquaculture and sport fisheries. This review integrates current knowledge on the biology, culture, and physiological adaptations of this species, emphasizing its potential for sustainable aquaculture. From a biological perspective, pejerrey exhibits a unique combination of genotypic and temperature‐dependent sex determination, making it a prime model for studying sex determination in vertebrates. From an aquaculture standpoint, many of the potential limitations of pejerrey farming have been addressed by focused research, such as the low batch fecundity, poor synchronization of maturation, and limited sperm availability are now almost completely mitigated by advances in photothermal and hormonal manipulation of maturation and broodstock husbandry. Osmoregulatory studies confirmed that pejerrey is a euryhaline species, thriving in brackish water, which enhances survival and stress tolerance across all life stages, resolving early misconceptions of pejerrey as a strictly freshwater fish. With survival under control, the low growth rate is now the next research challenge, although it is compensated for by the quality and high market value of the fish. Triploidy induction, interspecific hybridization with the Patagonian pejerrey, and thermal treatments for sex control offer promising avenues for growth improvement through reproductive suppression or monosex culture. The sequencing of its genome paves the way for genetic improvement via genomic selection and gene editing. Ongoing nutritional studies are key to optimizing diets, enhancing growth rates, and improving reproductive success. Further investigations on these and other areas should help realize the aquaculture potential of this economically significant species.

Comparative assessment of black carbon levels in public transit systems across three cities - Alejandro Perez Villasenor; Xudong Wang; Jill Baumgartner; Luis Miranda-Moreno (Transportation Research Part D: Transport and Environment, 2025)

Facial action units as biomarkers of postoperative pain in ovariohysterectomized bitches treated with cannabidiol and meloxicam - Alejandro Casas-Alvarado; Julio Martínez-Burnes; Patricia Mora-Medina; Ismael Hernández-Avalos; Agatha Miranda-Cortes; Adriana Domínguez-Oliva; Daniel Mota-Rojas (Research in Veterinary Science, 2025)

Integrating healthcare utilization databases for cancer ascertainment in a prospective cohort in a limited resource setting: the Mexican Teachers’ Cohort - Liliana Gómez-Flores-Ramos; Marion Brochier; Dalia Stern; Antonio García-Anaya; Adrian Cortés-Valencia; Jocelyn Jaen; Hugo R. Sánchez-Blas; Susana Lozano-Esparza; Andrés Catzin-Kuhlmann; Juan Eugenio Hernández-Ávila; Angélica Pon; Olga Rivera-Ontiveros; et al. (Cancer Causes & Control, 2025)

Identifying current trends in the environmental impacts linked to fishmeal and fish oil production in Peru - Alejandro Deville; Ian Vázquez-Rowe; Angel Avadí; Fernando Miranda; Ramzy Kahhat (Aquaculture, 2025)

Impacts of Artificial Light at Night (ALAN) on coastal ecosystems: A study on the herbivore Ampithoe valida with focus on sex-dependent responses - Nicole Jahnsen-Guzmán; Diego Quintanilla-Ahumada; Ricarda Blum; Alejandro F. Gadda; Oriana A. Amorin; Cristian Miranda-Benabarre; José Pulgar; Cristian Duarte; Macarena S. Valiñas (Marine Pollution Bulletin, 2025)

Leaching potential of heavy metals and metalloids in mining-impacted soils of central Mexico: Accelerated column tests and geochemical modeling - Luisa Fernanda Rueda-Garzón; Alejandro Carrillo-Chávez; Raúl Miranda-Avilés; Maria Jesús Puy Alquiza; Gabriela Zanor; Margarita Ramírez-Ramírez; Carolina Muñoz-Torres; Pooja Kshirsagar; Yanmei Li; Xu Liao; Daniela Kristell Calvo-Ramos (Journal of South American Earth Sciences, 2025)

An analysis of the spatial distribution of NO2 extremes in the metropolitan area of the valley of Mexico using a decision tree - Liliana Miranda-Aragón; Alejandro Ivan Aguirre-Salado (Stochastic Environmental Research and Risk Assessment, 2025)

An arbitrary waveform neurostimulator for preclinical studies: design and verification - Hipolito Guzman-Miranda; Alejandro Barriga-Rivera (Medical & Biological Engineering & Computing, 2025)
Neural electrostimulation has enabled different therapies to treat a number of health problems. For example, the cochlear implant allows for recovering the hearing function and deep brain electrostimulation has been proved to reduce tremor in Parkinson’s disease. Other approaches such as retinal prostheses are progressing rapidly, as researchers continue to investigate new strategies to activate targeted neurons more precisely. The use of arbitrary current waveform electrosimulation is a promising technique that allows exploiting the differences that exist among different neural types to enable preferential activation. This work presents a two-channel arbitrary waveform neurostimulator designed for visual prosthetics research. A field programmable gate array (FPGA) was employed to control and generate voltage waveforms via digital-to-analog converters. Voltage waveforms were then electrically isolated and converted to current waveforms using a modified Howland amplifier. Shorting of the electrodes was provided using multiplexers. The FPGA gateware was verified to a high level of confidence using a transaction-level modeled testbench, achieving a line coverage of 91.4%. The complete system was tested in saline using silver electrodes with diameters from 200 to 1000 µm. The bandwidth obtained was 30 kHz with voltage compliance ± 15 V. The neurostimulator can be easily scaled up using the provided in/out trigger ports and adapted to other applications with minor modifications. Graphical Abstract

Feasibility of nitrogen and phosphorus removal from treated wastewater using microalgae and potential microalgae use as biofertilizer - Alejandro Pérez Mesa; Paula Andrea Céspedes Grattz; Juan José Vidal Vargas; Luis Alberto Ríos; David Ocampo Echeverri; Alejandra María Miranda Parra (Journal of Water Process Engineering, 2025)

High throughput sequencing reveals mixed infections of impatiens necrotic spot virus and tomato brown rugose fruit virus in bell pepper crops in Mexico - María de los Ángeles Mora-Ugalde; Omar Alejandro Miranda-Campaña; Milagros Ramírez-Soto; José Luis Cruz-Jaramillo; Ignacio Javier Espinosa de los Reyes Bolaños; Juan Manuel Tovar-Pedraza; William M. Wintermantel; Alfredo Diaz-Lara (Journal of Plant Pathology, 2024)

Unraveling the chemistry of plant flammability: Exploring the role of volatile secondary metabolites beyond terpenes - Fabián Guerrero; Lorena Espinoza; Camilo Carmona; Melisa Blackhall; Carolina Quintero; Korina Ocampo-Zuleta; Susana Paula; Javier Madrigal; Mercedes Guijarro; Yulian Carrasco; Marcela A. Bustamante-Sánchez; Alejandro Miranda; et al. (Forest Ecology and Management, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Effect of a nutritional intervention based on an energy-reduced Mediterranean diet on environmental impact - Laura Álvarez-Álvarez; María Rubín-García; Facundo Vitelli-Storelli; Silvia García; Cristina Bouzas; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Mireia Malcampo; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; et al. (Science of The Total Environment, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

CRISPRi-induced transcriptional regulation of IAH1 gene and its influence on volatile compounds profile in Kluyveromyces marxianus DU3 - Luis A. Muñoz-Miranda; Andrea Catalina Zepeda-Peña; Leticia Casas-Godoy; Alejandro Pereira-Santana; Andrés Méndez-Zamora; Iliana Barrera-Martínez; Luis Rodríguez-Zapata; Anne Christine Gschaedler-Mathis; Luis J. Figueroa-Yáñez (World Journal of Microbiology and Biotechnology, 2024)

Disentangling the gut bacterial communities of the agave weevil, Scyphophorus acupunctatus (Coleoptera: Curculionidae) - Gabriela I. Salazar-Rivera; Alejandro Pereira-Santana; Ioreni Margarita Hernández-Velázquez; Mizraim Olivares-Miranda; Enrique Ibarra-Laclette; Anne C. Gschaedler Mathis; Jhony Navat Enríquez-Vara; Jesús Alejandro Zamora-Briseño (Symbiosis, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Remote sensing biodiversity monitoring in Latin America: Emerging need for sustained local research and regional collaboration to achieve global goals - Carol X. Garzon‐Lopez; Alejandro Miranda; Daniel Moya; Veronica Andreo (Global Ecology and Biogeography, 2024)
Aim Biodiversity monitoring at global scales has been identified as one of the priorities to halt biodiversity loss. In this context, Latin America and the Caribbean (LAC), home to 60% of the global biodiversity, play an important role in the development of an integrative biodiversity monitoring platform. In this review, we explore to what extent LAC has advanced in the adoption of remote sensing for biodiversity monitoring and what are the gaps and opportunities to integrate local monitoring into global efforts to halt biodiversity loss. Location Latin America and the Caribbean. Time period 1995 to 2022. Taxa studied Terrestrial organisms. Methods We reviewed the application of remote sensing for biodiversity monitoring in LAC aiming to identify gaps and opportunities across countries, ecosystem types and research networks. Results Our analysis illustrates how the use of remote sensing in LAC is disproportionately low in relation to the biodiversity it supports. Main conclusions Build upon this analysis, we present, discuss and offer perspectives regarding four gaps identified in the application of remote sensing for biodiversity monitoring in Latin America and the Caribbean, namely (1) alignment between remote sensing data resolution and ecosystem structure; (2) investment in research, institutions and capacity building within researchers and stakeholders; (3) decolonized practices that promote access to publishing outlets and pluralistic participation among countries that facilitate exchange of experiences and capacity building; and (4) development of networks within and across regions to advance in ground surveys, ensure access and to foster the use of remote sensing data.

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Corrigendum to “JM-20 treatment prevents neuronal damage and memory impairment induced by aluminum chloride in rats” [Neurotoxicology 87 (2021) 70–85] - Maylin Wong-Guerra; Yanay Montano-Peguero; Jeney Ramírez-Sánchez; Javier Jiménez-Martin; Luis Arturo Fonseca-Fonseca; Daniela Hernández-Enseñat; Yasmine Nonose; Odalys Valdés; Abel Mondelo-Rodriguez; Yaquelin Ortiz-Miranda; Gretchen Bergado; Tania Carmenate; et al. (NeuroToxicology, 2023)

Effects of solvent extracted organic matter from outdoor air pollution on human type II pneumocytes: Molecular and proteomic analysis - Alejandro Déciga-Alcaraz; Carmen Tlazolteotl Gómez de León; Jorge Morales Montor; Josefina Poblano-Bata; Yadira Margarita Martínez-Domínguez; M. Isabel Palacios-Arreola; Omar Amador-Muñoz; Carolina Rodríguez-Ibarra; Gustavo J. Vázquez-Zapién; Mónica M. Mata-Miranda; Yesennia Sánchez-Pérez; Yolanda I. Chirino (Environmental Pollution, 2023)

A firebreak placement model for optimizing biodiversity protection at landscape scale - Jaime Carrasco; Rodrigo Mahaluf; Fulgencio Lisón; Cristobal Pais; Alejandro Miranda; Felipe de la Barra; David Palacios; Andrés Weintraub (Journal of Environmental Management, 2023)

Meta-analysis of hydroxycinnamic acids into finishing lambs’ diet: Growth performance, antioxidant status, and meat quality - José Felipe Orzuna-Orzuna; Alejandro Lara-Bueno; Germán David Mendoza-Martínez; Luis Alberto Miranda-Romero (Small Ruminant Research, 2023)

Correction to: Dopamine removal from water by advanced oxidative processes with Fe/N‑doped carbon nanotubes - Anaí Laurel Leon; Nicolas Alejandro Sacco; Fernanda Miranda Zoppas; Rosario Galindo; Emilio Muñoz Sandoval; Fernanda Albana Marchesini (Environmental Science and Pollution Research, 2023)

Dopamine removal from water by advanced oxidative processes with Fe/N-doped carbon nanotubes - Anaí Laurel Leon; Nicolas Alejandro Sacco; Fernanda Miranda Zoppas; Rosario Galindo; Emilio Muñoz Sandoval; Fernanda Albana Marchesini (Environmental Science and Pollution Research, 2023)

Functionalized screen-printed electrodes for the thermal detection of Escherichia coli in dairy products - Rocio Arreguin-Campos; Margaux Frigoli; Manlio Caldara; Robert D. Crapnell; Alejandro Garcia-Miranda Ferrari; Craig E. Banks; Thomas J. Cleij; Hanne Diliën; Kasper Eersels; Bart van Grinsven (Food Chemistry, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Interference effects of oxyanions commonly found in natural waters on the catalytic reduction of nitrate in water - Nicolás Alejandro Sacco; Fernanda Miranda Zoppas; Thiago Favarini Beltrame; Eduardo Ernesto Miró; Fernanda Albana Marchesini (Environmental Science and Pollution Research, 2022)

Contamination assessment and potential sources of heavy metals and other elements in sediments of a basin impacted by 500 years of mining in central Mexico - Luisa Fernanda Rueda-Garzon; Raúl Miranda-Avilés; Alejandro Carrillo-Chávez; María Jesus Puy-Alquiza; Jorge Luis Morales-Martinez; Gabriela Zanor (Environmental Monitoring and Assessment, 2022)

First Records of the Invading Species Drosophila Nasuta (Diptera: Drosophilidae) in the Amazon - Hermes Fonseca de Medeiros; Márcia Pereira Monteiro; Antônio Wesley Barros Caçador; Camila Miranda Pereira; Catarina de Lurdes Bezerra Praxedes; Marlúcia Bonifácio Martins; Martín Alejandro Montes; Ana Cristina Lauer Garcia (Neotropical Entomology, 2022)

Bacteria in (vermi)composted organic wastes mostly survive when applied to an arable soil cultivated with wheat (Triticum sp. L.) - Alejandra Miranda-Carrazco; Claudia Chávez-López; Daniel Alejandro Ramírez-Villanueva; Luc Dendooven (Environmental Monitoring and Assessment, 2022)

Greenhouse gas emissions of biosolid and cow manure during composting and vermicomposting and when applied to soil cultivated with wheat (Triticum sp. L.) - Alejandra Miranda-Carrazco; Daniel Alejandro Ramírez-Villanueva; Luc Dendooven (Environmental Science and Pollution Research, 2022)

Seed dispersal distance, seed morphology, and recruitment in the Chilean sclerophyllous tree Quillaja saponaria: implications for passive restoration in a semiarid ecosystem - Inao Vásquez; Alejandro Miranda; Cristian A. Delpiano; Pablo I. Becerra (Plant Ecology, 2022)

Emergence and spread of the potential variant of interest (VOI) B.1.1.519 of SARS-CoV-2 predominantly present in Mexico - Abril Paulina Rodríguez-Maldonado; Joel Armando Vázquez-Pérez; Alberto Cedro-Tanda; Blanca Taboada; Celia Boukadida; Claudia Wong-Arámbula; Tatiana Ernestina Nuñez-García; Natividad Cruz-Ortiz; Gisela Barrera-Badillo; Lucía Hernández-Rivas; Irma López-Martínez; Alfredo Mendoza-Vargas; et al. (Archives of Virology, 2021)

Climate and Land Cover Trends Affecting Freshwater Inputs to a Fjord in Northwestern Patagonia - Jorge León-Muñoz; Rodrigo Aguayo; Rafael Marcé; Núria Catalán; Stefan Woelfl; Jorge Nimptsch; Ivan Arismendi; Camila Contreras; Doris Soto; Alejandro Miranda (Frontiers in Marine Science, 2021)
Freshwater inputs strongly influence oceanographic conditions in coastal systems of northwestern Patagonia (41–45°S). Nevertheless, the influence of freshwater on these systems has weakened in recent decades due to a marked decrease in precipitation. Here we evaluate potential influences of climate and land cover trends on the Puelo River (640 m 3 s –1 ), the main source of freshwater input of the Reloncaví Fjord (41.5°S). Water quality was analyzed along the Puelo River basin (six sampling points) and at the discharge site in the Reloncaví Fjord (1, 8, and 25 m depth), through six field campaigns carried out under contrasting streamflow scenarios. We also used several indicators of hydrological alteration, and cross-wavelet transform and coherence analyses to evaluate the association between the Puelo River streamflow and precipitation (1950–2019). Lastly, using the WEAP hydrological model, land cover maps (2001–2016) and burned area reconstructions (1985–2019), we simulated future land cover impacts (2030) on the hydrological processes of the Puelo River. Total Nitrogen and total phosphorus, dissolved carbon, and dissolved iron concentrations measured in the river were 3–15 times lower than those in the fjord. Multivariate analyses showed that streamflow drives the carbon composition in the river. High streamflow conditions contribute with humic and colored materials, while low streamflow conditions corresponded to higher arrival of protein-like materials from the basin. The Puelo River streamflow showed significant trends in magnitude (lower streamflow in summer and autumn), duration (minimum annual streamflow), timing (more floods in spring), and frequency (fewer prolonged floods). The land cover change (LCC) analysis indicated that more than 90% of the basin area maintained its land cover, and that the main changes were attributed to recent large wildfires. Considering these land cover trends, the hydrological simulations project a slight increase in the Puelo River streamflow mainly due to a decrease in evapotranspiration. According to previous simulations, these projections present a direction opposite to the trends forced by climate change. The combined effect of reduction in freshwater input to fiords and potential decline in water quality highlights the need for more robust data and robust analysis of the influence of climate and LCC on this river-fjord complex of northwestern Patagonia.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Landscape restoration in a mixed agricultural-forest catchment: Planning a buffer strip and hedgerow network in a Chilean biodiversity hotspot - José M. Rey Benayas; Adison Altamirano; Alejandro Miranda; Germán Catalán; Marco Prado; Fulgencio Lisón; James M. Bullock (Ambio, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Native forest loss in the Chilean biodiversity hotspot: revealing the evidence - Alejandro Miranda; Adison Altamirano; Luis Cayuela; Antonio Lara; Mauro González (Regional Environmental Change, 2017)

The invasive species Ulex europaeus (Fabaceae) shows high dynamism in a fragmented landscape of south-central Chile - Adison Altamirano; Jenny Paola Cely; Andrés Etter; Alejandro Miranda; Andres Fuentes-Ramirez; Patricio Acevedo; Christian Salas; Rodrigo Vargas (Environmental Monitoring and Assessment, 2016)

Influence of climate variations on Chascomús shallow lake thermal conditions and its consequences on the reproductive ecology of the Argentinian Silverside (Odontesthes bonariensis—Actinopterygii, Atherinopsidae) - Mariano Elisio; Alejandro Vitale; Leandro A. Miranda (Hydrobiologia, 2015)

Water quality, phytoplankton composition and growth of Litopenaeus vannamei (Boone) in an integrated biofloc system with Gracilaria birdiae (Greville) and Gracilaria domingensis (Kützing) - Luis Otavio Brito; Luis Alejandro Vinatea Arana; Roberta Borda Soares; William Severi; Rayzza Helena Miranda; Suzianny Maria Bezerra Cabral da Silva; Maria Raquel Moura Coimbra; Alfredo Olivera Gálvez (Aquaculture International, 2014)

Construction of aboveground biomass models with remote sensing technology in the intertropical zone in Mexico - Carlos Arturo Aguirre-Salado; Eduardo Javier Treviño-Garza; Oscar Alberto Aguirre-Calderón; Javier Jiménez-Pérez; Marco Aurelio González-Tagle; José René Valdez-Lazalde; Liliana Miranda-Aragón; Alejandro Iván Aguirre-Salado (Journal of Geographical Sciences, 2012)

Professional Capacity Building: the Missing Agenda in Conservation Priority Setting - Jon Paul Rodríguez; Kathryn M. Rodríguez‐Clark; María A. Oliveira‐Miranda; Tatjana Good; Alejandro Grajal (Conservation Biology, 2006)

Characterization of brain gonadotropin-releasing hormone (GnRH) molecular variants in brain extracts from different perciform fishes from Antarctic waters - Leandro A. Miranda; Alejandro D. Montaner; Martín Ansaldo; Jorge M. Affanni; Gustavo M. Somoza (Polar Biology, 1999)